tìm m để hàm số y=f(x)=(căn (m^2 + 4) – m). x^2 – 2xm + 5 thỏa mãn điều kiện f(0)=f(1)

Question

tìm m để hàm số y=f(x)=(căn (m^2 + 4) – m). x^2 – 2xm + 5 thỏa mãn điều kiện f(0)=f(1)

in progress 0
Rose 3 giờ 2021-09-07T12:59:29+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-07T13:00:52+00:00

    CHÚC BẠN HỌC TỐT !!!!!!!!!

    Đáp án:

    $m = \dfrac{\sqrt{2}}{2}$

    Giải thích các bước giải:

    Với $x = 0$

    $=> y = f(0) = (\sqrt{m² + 4} – m).0² – 2.0.m + 5 = 5$

    Với $x = 1$

    $=> y = f(1) = (\sqrt{m² + 4} – m).1² – 2.1.m + 5$

                         $= \sqrt{m² + 4} – m – 2m + 5$

                         $= \sqrt{m² + 4} – 3m + 5$

    Để $f(0) = f(1)$

    $⇔ 5 = \sqrt{m² + 4} – 3m + 5$

    $⇔ \sqrt{m² + 4} = 3m$

    Vì $\sqrt{m² + 4} ≥ 2$ với mọi $m$

    $=> 3m ≥ 2 ⇔ m ≥ \dfrac{2}{3}$

    Khi đó, ta có:

           $\sqrt{m² + 4} = 3m$

    $⇔ m² + 4 = 9m²$

    $⇔ 8m² = 4$

    $⇔ m² = \dfrac{1}{2}$

    $⇔$ \(\left[ \begin{array}{l}m = \dfrac{\sqrt{2}}{2} (T/m)\\m = – \dfrac{\sqrt{2}}{2} (Loại)\end{array} \right.\) 

    Vậy $m = \dfrac{\sqrt{2}}{2}.$

    0
    2021-09-07T13:01:17+00:00

    $y=f(x)=(\sqrt{m^{2}+4}-m)x^{2}-2mx+5$
    Ta có: $f(0)=(\sqrt{m^{2}+4}-m).0-2m.0+5=5$
    $f(1)=(\sqrt{m^{2}+4}-m).1-2m.1+5\\=\sqrt{m^{2}+4}-3m+5$
    Để $f(0)=f(1)\Leftrightarrow 5=\sqrt{m^{2}+4}-3m+5\\\Leftrightarrow \sqrt{m^{2}+4}=3m\\\Leftrightarrow m^{2}+4=9m^{2}\\\Leftrightarrow 8m^{2}=4\\\Leftrightarrow m^{2}=\frac{1}{2}\\\Leftrightarrow m=\frac{\sqrt{2}}{2}$

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )